Androgen Receptors in Epithelial Cells Regulate Thymopoiesis and Recent Thymic Emigrants in Male Mice - Wilhelmson, Anna S.; Lantero Rodriguez, Marta; Johansson, Inger; Svedlund Eriksson, Elin; Stubelius, Alexandra; Lindgren, Susanne; Fagman, Johan Bourghardt; Fink, Pamela J.; Carlsten, Hans; Ekwall, Olov; Tivesten, Åsa (Frontiers in Immunology, 2020)
Androgens have profound effects on T cell homeostasis, including regulation of thymic T lymphopoiesis (thymopoiesis) and production of recent thymic emigrants (RTEs), i.e. immature T cells that derive from the thymus and continue their maturation to mature naïve T cells in secondary lymphoid organs. Here we investigated the androgen target cell for effects on thymopoiesis and RTEs in spleen and lymph nodes. Male mice with a general androgen receptor knockout (G-ARKO), T cell- specific (T-ARKO), or epithelial cell-specific (E-ARKO) knockout were examined. G-ARKO mice showed increased thymus weight and increased numbers of thymic T cell progenitors. These effects were not T cell-intrinsic, since T-ARKO mice displayed unaltered thymus weight and thymopoiesis. In line with a role for thymic epithelial cells (TECs), E-ARKO mice showed increased thymus weight and numbers of thymic T cell progenitors. Further, E-ARKO mice had more CD4+ and CD8+ T cells in spleen and an increased frequency of RTEs among T cells in spleen and lymph nodes. Depletion of the androgen receptor in epithelial cells was also associated with a small shift in the relative number of cortical (reduced) and medullary (increased) TECs and increased CCL25 staining in the thymic medulla, similar to previous observations in castrated mice. In conclusion, we demonstrate that the thymic epithelium is a target compartment for androgen-mediated regulation of thymopoiesis, splenic T cells, and RTEs in secondary lymphoid organs.